2015
DOI: 10.4244/eijy14m07_18
|View full text |Cite
|
Sign up to set email alerts
|

Invasive management without stents in selected acute coronary syndrome patients with a large thrombus burden: a prospective study of optical coherence tomography guided treatment decisions

Abstract: 2 STRUCTURED ABSTRACT Aims:To assess whether a strategy of invasive management without stents in selected acute coronary syndrome (ACS) patients with a large thrombus burden (LTB) might be feasible and safe. Methods and results:We performed a prospective non-randomised observational cohort study of invasive treatment decisions guided by optical coherence tomography (OCT) in selected ACS patients with LTB.Among 852 ACS patients who had undergone invasive coronary angiography, 101(11.8%) patients with large thro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 32 publications
0
21
1
6
Order By: Relevance
“…Cafri et al 9 reported a lower rate of thrombus-related angiographic events in patients treated with DS 4.9 days after the first procedure (4% versus 27% for IS; P=0.03). 24 showed that it can take >7 days to achieve complete thrombus regression.…”
Section: Discussionmentioning
confidence: 99%
“…Cafri et al 9 reported a lower rate of thrombus-related angiographic events in patients treated with DS 4.9 days after the first procedure (4% versus 27% for IS; P=0.03). 24 showed that it can take >7 days to achieve complete thrombus regression.…”
Section: Discussionmentioning
confidence: 99%
“…38 Finally, a recent study investigated the use of OCT to guide the management of patients with ACS and large thrombus burden. 39 The study involved 852 patients with ACS. Of these patients, 101 had large thrombus burden and underwent thrombectomy to restore Thrombolysis In Myocardial Infarction (TIMI) 3 flow.…”
Section: Optimising Percutaneous Coronary Interventionmentioning
confidence: 99%
“…Although the limited depth of penetration of OCT imaging may limit the assessment of plaque burden and deep tissue structures, prior work has validated the ability of OCT to accurately discriminate different types of plaque and to identify features associated with plaque vulnerability for thrombosis and rupture, which are predominantly located in the superficial part of the vessel. Studies are now underway investigating the use of OCT in guiding clinical decision making, 55 and further improvements in OCT technology should expand its utility in both research and clinical settings.…”
Section: Discussionmentioning
confidence: 99%